Effect of curcumin-encapsulated Pluronic® F-127 over duo-species biofilm of Streptococcus mutans and Candida albicans - dos Santos, Diego Dantas Lopes [UNESP]; Besegato, João Felipe [UNESP]; de Melo, Priscila Borges Gobbo [UNESP]; Junior, João Augusto Oshiro [UNESP]; Chorilli, Marlus [UNESP]; Deng, Dongmei; Bagnato, Vanderlei Salvador; de Souza Rastelli, Alessandra Nara [UNESP] (Springer Nature, 2022)
To assess the effect of curcumin-encapsulated Pluronic® F-127 (Cur-Plu) during antimicrobial photodynamic therapy (aPDT) over duo-species biofilm of Streptococcus mutans and Candida albicans. Thermal analysis, optical absorption, and fluorescence spectroscopy were evaluated. Minimum inhibitory concentration (MIC) and minimum bactericidal/fungal concentration were obtained. The biofilms were cultured for 48 h at 37 °C and treated according to the groups: P + M + L + (photosensitizer encapsulated with Pluronic® F-127 + light); P + D + L + (photosensitizer incorporated in 1% DMSO + light); P − M + L + (no Pluronic® F-127 + light); P − D + L + (1% DMSO + light); P − L + (Milli-Q water + light); P + M + L − (photosensitizer encapsulated with Pluronic® F-127 no light); P + D + L − (photosensitizer in 1% DMSO, no light); P − M + L − (Pluronic® F-127 no light); P − D + L − (1% DMSO, no light); P − L − (Milli-Q water, no light; negative control group); CHX (0.2% chlorhexidine, positive control group); and NYS (Nystatin). Dark incubation of 5 min was used. The groups that received aPDT were irradiated by blue LED (460 nm, 15 J/cm2). Cell viability of the biofilms was performed by colony-forming units (CFU/mL) and confocal microscopy. Two-way ANOVA followed by Tukey’s post hoc test was used at a significance level of 5%. P + D + L + and P + M + L + groups exhibited better log-reduction for both Candida albicans and Streptococcus mutans biofilms than P − M + L + , P − L + , and P − D + L + experimental groups. Furthermore, P + M + L + and P + D + L + showed greater reduction for Candida albicans than for Streptococcus mutans. aPDT mediated by Cur-Plu can be a potential strategy for biofilm control against duo-species biofilm of Streptococcus mutans and Candida albicans.
Keywords: Biofilms; Candida albicans; Curcumin; Micelles; Photochemotherapy; Streptococcus mutans